Morphology-photovoltaic property correlation in perovskite solar cells: One-step versus two-step deposition of CH3NH3PbI3 - Jeong-Hyeok Im; Hui-Seon Kim; Nam-Gyu Park (APL Materials, 2014)
Perovskite CH3NH3PbI3 light absorber is deposited on the mesoporous TiO2 layer via one-step and two-step coating methods and their photovoltaic performances are compared. One-step coating using a solution containing CH3NH3I and PbI2 shows average power conversion efficiency (PCE) of 7.5%, while higher average PCE of 13.9% is obtained from two-step coating method, mainly due to higher voltage and fill factor. The coverage, pore-filling, and morphology of the deposited perovskite are found to be critical in photovoltaic performance of the mesoporous TiO2 based perovskite solar cells.